Teacher-Child Interactions of First-Grade Students Who Have Learning Problems. - Parker, Randall; Larsen, Stephen; Roberts, Timothy (Elementary School Journal, 1981)
The article discusses a study of teacher-child interactions of students who have learning problems. The purpose of the study is to examine the teacher-child verbal interactions in first-grade classrooms as the interaction relate to students with varying levels of achievement growth and risk of developing learning problems.